Peran Organisasi Siswa Intra Sekolah (OSIS) untuk Menerapkan Nilai-Nilai Karakteristik Moral Siswa di Madrasah Aliyah Hidayatul Mubtadin Sidoharjo Jati Agung Lampung Selatan - Firman Ferdiansyah (Departement of Mathematics Education, 2024)
This study aims to examine the role of the Intra-School Student Organization (OSIS) in implementing the moral characteristic values ​​of students at Madrasah Aliyah Hidayatul Mubtadin Sidoharjo, Jati Agung, South Lampung. OSIS as a forum for student organizations has an important responsibility in developing students' character and morality. The method used in this study is descriptive qualitative, which involves interviews, observations, and document analysis. The results of the study indicate that OSIS plays an active role in integrating moral values ​​through various activities, such as leadership training, social service programs, and seminars on ethics and religious values. In addition, OSIS also functions as a communication bridge between students and the school in supporting the implementation of positive character. These findings indicate that through OSIS activities, students not only learn about responsibility and leadership, but also internalize moral values ​​that can shape their personalities. This study recommends improving the OSIS program to be more diverse and focus on character development so that students can be more optimal in implementing moral values ​​in their daily lives.